Хірургічна тиреоїдна патологія у хворих гемодіалізної популяції - Ксенофонтов, С. С.; Гудинов, І. Д.; Білозерцев, О. М.; Ксенофонтова, Г. С. (Clinical Endocrinology and Endocrine Surgery, 2009)
14 patients with surgical thyroid pathology and protracted experience of replace kidney therapy, including patients (3) to which in different terms from a moment beginning of replace kidney therapy the executed transplantation of kidney were under our observation. A troubleshooting routine and principles of treatment is lighted up. Information is resulted on the executed operative interventions their features and results of histological research of operating material. It is underlined that thyroid pathology at the patients of haemodialysing population is immediate, difficult and in a great deal contradictory problems modern surgery which needs subsequent scientifically-evidential, system-organ approach to the decision of questions of practical orientation. Conclusions are given.